1998
DOI: 10.1002/(sici)1097-4547(19980501)52:3<342::aid-jnr10>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole attenuates cortical lesion size, but not hippocampal neuronal loss, following traumatic brain injury in the rat

Abstract: The neuroprotective effects of Riluzole, a compound with several mechanisms of action including the inhibition of sodium channel activity and glutamate release, were evaluated in a rat model of parasagittal fluid-percussion (FP) brain injury. Male Sprague-Dawley rats (350-400 g, n = 17) were anesthetized with sodium pentobarbital (60 mg/kg i.p.) and subjected to parasagittal FP brain injury of moderate severity (2.3-2.5 atm). Fifteen min following injury, animals randomly received an i.v. bolus of either Riluz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…Likewise, calpain inhibition suppressed axonal pathology in traumatic brain injury (Buki et al, 1999), anoxic optic nerve (Jiang and Stys, 2000), and traumatic optic nerve stretch injury (Witgen et al, 2001). It has also been shown that NaCh blockers improve functional outcome and reduce axonal pathology in models of spinal cord crush injury (Teng and Wrathall, 1997;Rosenberg et al, 1999;Schwartz and Fehlings, 1999) as well as functional outcome in traumatic brain injury Zhang et al, 1998). Taken in context with the present results, these therapeutic approaches may show benefit by interrupting the feed-forward process initiated by NaCh dysfunction after traumatic axonal injury.…”
Section: Discussionsupporting
confidence: 69%
“…Likewise, calpain inhibition suppressed axonal pathology in traumatic brain injury (Buki et al, 1999), anoxic optic nerve (Jiang and Stys, 2000), and traumatic optic nerve stretch injury (Witgen et al, 2001). It has also been shown that NaCh blockers improve functional outcome and reduce axonal pathology in models of spinal cord crush injury (Teng and Wrathall, 1997;Rosenberg et al, 1999;Schwartz and Fehlings, 1999) as well as functional outcome in traumatic brain injury Zhang et al, 1998). Taken in context with the present results, these therapeutic approaches may show benefit by interrupting the feed-forward process initiated by NaCh dysfunction after traumatic axonal injury.…”
Section: Discussionsupporting
confidence: 69%
“…66,67,87,88 Therefore, cell counts were performed at a site 1.8 mm posterior to bregma in these regions with damaged neurons identified by criteria previously established in the rat. 52,98 One slide per animal was randomly chosen, and cell counts were performed at a magnification of ϫ 200. Starting at the junction of CA2 and CA3, 23 three consecutive microscopic fields were counted in the hippocampal CA3 pyramidal layer.…”
Section: Motor Functionmentioning
confidence: 99%
“…To count cells in the hilum of the dentate gyrus of the hippocampus, the medial end of the CA3 cell layer was located on the identical slide, and all cells between the upper and the lower blade of the dentate gyrus were counted according to a protocol established for the rat. 52,98 All cell counting was performed by one investigator (S.H.) who was blinded to the injury status of each animal.…”
Section: Motor Functionmentioning
confidence: 99%
“…Sections from bregma -0.3 to bregma -6.3 (32) were stained with hematoxylin and eosin, and the area of the contralateral and ipsilateral cortexes was then measured using a light microscope and image analysis system, as described previously (33). The cortexes of both hemispheres were outlined by hand by an evaluator blinded to injury and shock status, and the cortical areas were computed by the calibrated image analysis program.…”
Section: Assessment Of Cortical Tissue Lossmentioning
confidence: 99%